On Variable Sum Exdeg Indices of Quasi-Tree Graphs and Unicyclic Graphs - Xiaoling Sun; Jianwei Du (Discrete Dynamics in Nature and Society)
In this work, by using the properties of the variable sum exdeg indices and analyzing the structure of the quasi-tree graphs and unicyclic graphs, the minimum and maximum variable sum exdeg indices of quasi-tree graphs and quasi-tree graphs with perfect matchings were presented; the minimum and maximum variable sum exdeg indices of unicyclic graphs with given pendant vertices and cycle length were determined.